Tracing the Effects of Mobbing on the Performance of Engineers: An Evidence of a Telecom Sector - Fazal Rehman,; Rosman Md Yusoff,; Fadillah Ismail, (Journal of Social Transformation and Regional Development, 2019)
This study aims at investigating the effects of mobbing in losing the performance of engineers in the telecom sector of Pakistan. Precisely, it assesses the effects of mobbing on the job involvement, creativity, and efficiency of engineers. This study utilizes a quantitative approach to collect data through questionnaire based survey from the engineers of four telecommunication companies in urban areas of Pakistan. Data was analyzed by descriptive statistics and simple regression. Results indicate that mobbing has negative and significant relationship with the performance of engineers in the telecom sector of Pakistan. Mobbing has negative but significant relationship with job involvement, creativity and efficiency of engineers in the telecom sector of Pakistan. This study appraises to marketing and management professionals who are planning and implementing strategies in developed areas to enhance their services to control over mobbed behavior in working environment. The findings suggest that mobbing can lose the performance of engineers